Suporte à aprendizagem informal e confiança interpessoal: um estudo com trabalhadores do setor de TI - Silva, Cátia Camila da (2020)
The current context of organizations is characterized by an environment driven by innovations and the speed of the need for change. Knowledge occupies a central place in this increasingly complex and dynamic environment, being considered one of the basic organizational strategic resources for obtaining competitive advantages. In this context, several factors started to be observed as drivers of knowledge, among them informal learning, which can be considered as the result of social interaction, learning through practice and the organizational context. At the same time, interpersonal trust has been identified as one of the main reasons for people to cooperate with each other in the workplace. Considering that there may be a connection between these constructs, this study was developed with the purpose of investigating the relationship and influence between Support for Informal Learning and Interpersonal Trust from the perspective of IT company workers, who work in software development in companies located in the central region of Rio Grande do Sul. To achieve this goal, a descriptive, quantitative research was carried out. IT company workers answered a questionnaire based on Coelho Jr.'s Learning Support Scale (LSS) (2009), and Nyhan's Interpersonal Confidence Measure (2000) and Oh and Park (2011), which was validated nationally by Andrade (2017). In the quantitative analysis, the data were described using descriptive statistics, exploratory factor analysis, Pearson's correlation and by multiple regression, observing Cronbach's alpha indicator, with the aid of the SPSS software. In the descriptive analysis of the sample, the profile of the respondents showed the predominance of the male gender, of relatively young people and with a high level of education. In reference to support for informal learning, the presence of 4 factors was identified, totaling 27 variables, containing three factors more than the original unifatorial model proposed by Coelho Jr. (2009). Together, the four factors explained in 64.21% the perception of support for informal learning in the total sample. With regard to Interpersonal Trust, the factor analysis resulted in 2 factors, composed of 8 variables, maintaining the original model proposed by Nyhan (2000), Oh and Park (2011) and Andrade (2017). In Pearson's correlation analysis, the results with the greatest intensity between the two constructs were between the dimensions of Trust in superior and Support from the boss, and Trust in colleagues and Support from colleagues. In addition, through multiple regression analyzes it was found that interpersonal trust has an influence in supporting informal learning in the workplace. The model of this study with the greatest explanatory power was represented by the variable Support for general informal learning, whose variance was explained in 57.4% by the factors Trust in superiors and Trust in colleagues, followed by the Support model of the boss, where variance was explained 54.4% also due to the dimensions of Trust in superior and Trust in colleagues. The main results found indicate that support for informal learning is positively related to interpersonal trust. The observations that emerge from the results of this research suggest that workers who trust their colleagues and superiors are more likely to share knowledge and help colleagues, with interpersonal trust being a fundamental asset that drives the generation of knowledge in organizations. These results reveal that the technology companies, inserted in a market of changes in great speed, find in the trust between colleagues and superiors and in the work teams, a support in the search to remain competitive, being updated in a fast and constant way.